Sentidos e significados atribuídos à “escola”, para a família e para o aluno com dificuldades de aprendizagem - Miranda, Santareno Augusto (2014)
The objective of this work is to identify the senses and meanings assigned to "school” for the student with learning difficulties and the student’s family. It was used as a reference the Social Community Psychology and the assumption that all human knowledge depends on the limits imposed by their own reality. The method was based on qualitative epistemology and it was conducted in a private school. A questionnaire was applied to two parents and an interview was made to four students who presented learning difficulties. The results showed that the scientific concepts of "school" and "family” for students with learning difficulties are related to "tasks”, "meeting”, "learning" and "assistance", which means that there is a practical relation connected to some activities or obligations performed by the student. The results for the students’ parents reinforced even more this perception since the concepts are related to "School Calendar”, "Parent-Teacher Conference", "School Report" and "Tutoring". Both the sense and the meaning refer to a more objective and practical terms and it is strongly supported in everyday actions. As a final consideration, it was observed that parents who are actively involved in the mechanisms of communication between school and family can have a broader concept of school as a family social obligation and understand that these elements are part of the teaching-learning process. However, parents that nor following the school calendar or attending meetings tend to have an abstract sense of the school and this fragmented sense tends to influence a child indirectly to the concept of school and it may impair their learning process. When it comes to learning difficulties, parents’ involvement in school is a social subjectivity that can be considered as an important connection to help students with learning difficulties.